RANCANG BANGUN SISTEM INFORMASI INVENTORY BARANG PADA PT RAJAWALI BAHAN BANGUNAN BERBASIS WEB MENGGUNAKAN REORDER POINT (ROP): (Stok Barang pada PT. Rajawali Bahan Bangunan) - Ridwan; Bagus Wahyu Pandhito; Yose Eduar Muda (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
This study aims to design and develop a web-based inventory information system using the Reorder Point (ROP) method at PT. Rajawali Bahan Bangunan. By employing the Research and Development (R&D) research method and the Waterfall system development method, the system is designed to facilitate stock management, monitor minimum inventory levels, and support decision-making in reordering items. The system is built as a website to improve accessibility, featuring automatic reorder point calculations to optimize inventory management. The results of this study indicate that the designed system is effective in enhancing efficiency, accuracy, and timeliness in inventory management at PT. Rajawali Bahan Bangunan.